The Dynamics of Burnout in Elementary School Teachers: The Role of Work Stress and Emotional Intelligence - Fricylya, Fricylya; Chaiyanda, Yumico; Ramadhan Emha Damanik, Kevin; Rizky Polanta, Feby; Hartini, Sri; El Akmal, Mukhaira; Atrizka, Diny (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2025)
Work stress and emotional intelligence were crucial factors in determining individual performance dynamics in various environments, especially in work and academic contexts. High levels of work stress negatively impacted individual well-being, while emotional intelligence played a role in effectively managing pressure. This study aimed to analyze the influence of work stress and emotional intelligence on the dependent variable to understand how these two factors interacted in shaping individual responses to pressure. This study used a quantitative approach with regression analysis to identify the relationship between the examined variables. The results showed that work stress had a positive and significant influence on the dependent variable, while emotional intelligence had a negative and significant influence. Individuals with high levels of work stress tended to experience an increase in the dependent variable, whereas individuals with high emotional intelligence were better able to manage pressure and reduce its impact on the dependent variable. The implications of this study emphasized the importance of organizational strategies in managing work stress and enhancing emotional intelligence to create a healthier and more productive environment in both the workplace and academic settings, as well as opening opportunities for further research by adding other relevant variables. Stres kerja dan kecerdasan emosional menjadi faktor krusial dalam menentukan dinamika kinerja individu di berbagai lingkungan terutama dalam konteks pekerjaan dan akademik. Tingginya tingkat stres kerja berdampak negatif terhadap kesejahteraan individu sedangkan kecerdasan emosional berperan dalam mengelola tekanan secara efektif. Penelitian ini bertujuan menganalisis pengaruh stres kerja dan kecerdasan emosional terhadap variabel dependen guna memahami bagaimana kedua faktor tersebut berinteraksi dalam membentuk respons individu terhadap tekanan. Penelitian ini menggunakan pendekatan kuantitatif dengan metode analisis regresi untuk mengidentifikasi hubungan antara variabel yang diteliti. Hasil penelitian menunjukkan stres kerja memiliki pengaruh positif dan signifikan terhadap variabel dependen sedangkan kecerdasan emosional memiliki pengaruh negatif dan signifikan. Individu dengan tingkat stres kerja tinggi cenderung mengalami peningkatan dalam variabel dependen sedangkan individu dengan kecerdasan emosional tinggi lebih mampu mengelola tekanan dan mengurangi dampaknya terhadap variabel dependen. Implikasi penelitian ini menekankan pentingnya strategi organisasi dalam mengelola stres kerja dan meningkatkan kecerdasan emosional untuk menciptakan lingkungan lebih sehat dan produktif baik di dunia kerja maupun dalam setting akademik serta membuka peluang penelitian lanjutan dengan menambahkan variabel lain yang relevan.